LEGAL PLURALISM IN BUSINESS DISPUTE RESOLUTION: A Socio-Legal Analysis of Customary Commercial Practices in Jambi, Indonesia - Evi Ariyani; Layyin Mahfiana; Luthfiana Zahriani; Masrukhin Masrukhin; Jaka Susila (Fakultas Syariah, 2026)
Business dispute settlement in Indonesia remains dominated by formal institutions that are often costly, complex, and socially unresponsive. In highly plural regions like Jambi, commercial resolutions integrate state law and customary law mechanisms within local economic relations. This socio-legal study examines the role of customary law in business dispute resolution and its standing within Indonesia's legal pluralism framework, combining normative business law with empirical data on local commercial practices. The findings reveal that customary dispute mechanisms are vital for maintaining social harmony, achieving substantive justice, and sustaining commercial trust. This efficacy stems from communal values, customary authorities, and shared social norms, often outperforming formal systems. Crucially, this study contributes to reconstructing legal pluralism theory by positioning customary law as a functional alternative dispute resolution (ADR) mechanism in modern commerce. Beyond its local scope, these insights offer a novel paradigm for global legal pluralism, demonstrating how non-State, indigenous normative orders can effectively govern modern business relations while challenging the Western-centric hegemony of formalistic arbitration. Ultimately, this research provides a scalable framework and blueprint for Global South countries to design sustainable, socially responsive, and culturally anchored commercial dispute resolution systems.Penyelesaian sengketa bisnis di Indonesia masih didominasi oleh lembaga formal yang seringkali berbiaya tinggi, rumit, dan kurang responsif secara sosial. Di wilayah plural seperti Jambi, penyelesaian komersial mengintegrasikan hukum negara dan mekanisme hukum adat dalam relasi ekonomi lokal. Studi sosio-legal ini menguji peran hukum adat dalam sengketa bisnis dan kedudukannya dalam kerangka pluralisme hukum Indonesia, memadukan analisis normatif hukum bisnis dengan data empiris praktik komersial lokal. Temuan menunjukkan bahwa mekanisme adat vital untuk menjaga harmoni sosial, mencapai keadilan substantif, dan mempertahankan kepercayaan bisnis karena efektivitas nilai komunal dan otoritas adatnya. Secara krusial, studi ini berkontribusi merekonstruksi teori pluralisme hukum dengan memosisikan hukum adat sebagai penyelesaian sengketa alternatif (ADR) yang fungsional dalam perdagangan modern. Di luar konteks lokal, temuan ini menawarkan paradigma baru bagi pluralisme hukum global, membuktikan bahwa tatanan normatif adat non-negara dapat mengatur hubungan bisnis modern secara efektif sekaligus menantang hegemoni Barat dalam arbitrase formalistik. Pada akhirnya, penelitian ini menyediakan kerangka kerja dan cetak biru bagi negara-negara Global South untuk merancang sistem penyelesaian sengketa komersial yang berkelanjutan, responsif secara sosial, dan berakar pada budaya lokal.